ANALISIS INDEK KEPUASAN MASYARAKAT PDAM KOTA PEKALONGAN - Choliq Sabana; Siti Nurhayati; Alvis Muryodewanto (Jurnal Ekonomi Dan Bisnis, 2016)
Public services such as those operated by PDAM Pekalongan City still found manyweaknesses that can not meet the expected quality of the community . It is characterized by thepresence of various public complaints . the importance of  serving the water supply PDAM Pekalonganconsiders it important for information to the Public Satisfaction Index (HPI ) in order to improve qualityof service Surveys are intended to : 1 ) Identify and analyze the weaknesses of each of the elements ofservice delivery PDAM Pekalongan and 2 ) Measure the community Satisfaction Index (HPI ) PDAMKota Pekalongan . The survey results show that, in general , PDAM service performance Pekalongancategorized as "good" with a score of 75.71 . There are three elements to the status of serviceperformance Excellent ( Attitude Officer , comfort , and environmental safety services office ) , thereare nine elements of the status of service performance Good ( products , procedures Services ,completeness attributes , justice services , human resources capabilities , Fairness Cost , Certainty Costservices , Assurance services Schedule ) , There are four elements to the status of service performanceGood Enough ( Delivery System , service requirements , responsibility Officer , and Speed in Service )Keyword: PDAM Kota Pekalongan, IKM, Kepuasan